Wissen – Macht – Subjekt(e). Dimensionen historischer Diskursanalyse am Beispiel des Männerbunddiskurses im Wilhelminischen Kaiserreich - Bruns, Claudia (Österreichische Zeitschrift für Geschichtswissenschaften, 2005)
The article examines three significant aspects of discourse analysis: the production of scientific knowledge, power-relations, and the modern subject. The author gives a brief definition of these terms from a Foucauldian perspective and outlines the advantages of discourse analysis compared to other historical methods and theories (such as the history of ideas, classical social history, and ideological criticism). As the author points out, discourse analysis allows for the conceptualization of fiction and reality, theory and practice, culture and politics in a more integrated fashion than the other, above-mentioned approaches. Special emphasis is placed on the need to integrate the subject – with its own forms of physical, emotional, and psychological self-perception and self-expression – into discourse analysis. In addition to this theoretical discussion, the article includes a detailed analysis of male-bonding discourses in the German Empire, which provide a useful example of how discourse analysis can fully integrate the dimensions of knowledge, power and the subject.